Pengaruh Pemberian Susu Skim dengan Pengencer Tris Kuning Telur terhadap Daya Tahan Hidup Spermatozoa Sapi pada Suhu Penyimpanan 5ºC - Widjaya, Nilawati (Universitas Sebelas Maret (UNS), 2011)
The objective of the study was to determine the effect of skim milk and Tris yolkextender on the viability bovine spermatozoa at 5 ºC. This study used Simmental bull semen. The design used was Randomized Design Group (RAK) with 5 treatments and 5 groups of ejaculate. The treatments were: P0 = skim milk 100% without Tris yolk extender; P1 = 95% skim milk + 5% Tris yolk extender, P2 = 90% skim milk + Tris yolk extender 10%, P3 = skim milk 85% + Tris yolk extender 15%, P4 = skim milk 80% + Tris yolk extender 20%. The observed variables were the percentage of live spermatozoa and the motility of spermatozoa after storage for 2 days at 5ºC. Skim milk with Tris yolk extender affect the viability and motility of spermatozoa stored at 5ºC (P<0.01). Provision of extender up to 15% gave the best results and suppressed the decline in the viability of spermatozoa storaged for 2 days at 5ºC.Key words: skim milk, spermatozoa, Tris yolk extender, viability